Flux decay during thermonuclear X-ray bursts: Decay rate analysis with the dynamic power-law index method - Kuuttila, Jere (fi=Turun yliopisto|en=University of Turku|, 2017)
The cooling of type-I X-ray bursts can be used to probe the nuclear burning conditions in neutron star envelopes.The flux decay of the bursts has been traditionally modelled with an exponential, even if theoretical considerations predict power-law-like decays. In this work I have analysed a total of 540 type-I X-ray bursts from five low mass X-ray binaries observed with the Rossi X-ray Timing Explorer. The bursts were grouped according to the source spectral state during which they were observed (hard or soft), flagging those bursts that showed signs of photospheric radius expansion (PRE) The decay phase of all the bursts were then fitted with a dynamic power-law index method. This method provides a new way of probing the chemical composition of the accreted material.The results show that the power-law decay index is variable during the burst tails. In the presumably helium-rich sources 4U 1728-34 and 3A 1820-303 the variations are small and the cooling of the bursts can be qualitatively described with simple cooling models. The cooling in the hydrogen-rich sources 4U 1608-52, 4U 1636-536, and GS 1826-24, instead, is clearly different and it depends on the spectral states and whether PRE occurred or not. Especially the hard state bursts behave differently than the models predict, exhibiting a peculiar rise in the cooling index at low burst fluxes, which suggests that the cooling in the tail is much faster than expected.The results indicate that the drivers of the bursting behaviour are not only the accretion rate and the chemical composition of the accreted material, but also the cooling is somehow linked to the spectral states. The latter suggests that the properties of the burning layers deep in the neutron star envelope might be impacted differently depending on the spectral state.The results of this thesis have been published also in a separate article in Kuuttila et al. (2017)